Procurement and Politics Strategies of Defence Acquisition in Canada and Australia - Migone, Andrea (Springer Nature, 2023)
This open access book compares the experiences of large-scale military procurement in Canada and Australia. Focusing on the recent frigate and jet-fighter programmes, it demonstrates how delays suffered in delivering weapons systems and platforms in these countries have been caused by misalignments between the strategic requirements set out by the armed forces and government defence policies. By bringing the insights of public management and administration to those of defence studies, the book presents policy options that will help improve the nature of future large-project military procurement. It will appeal to scholars and students of public administration, public management, and defence studies, as well as practitioners and policymakers.